English Grammar Checker - Ghosalkar, Pratik; Malagi, Sarvesh; Nagda, Vatsal; Mehta, Yash; Kulkarni, Pallavi (International Journal of Computer Sciences and Engineering, 2025)
Language is the prime means of communication used by the individuals. It is the tool everyone uses to express the greater part of ideas and emotions. The usually poor quality of grammar leaves a bad impression on the reader. Therefore, there is a need for grammar checkers. We propose a grammar checking system by means of ‘Syntax Analysis’. [1][9]Syntax refers to the arrangement of words in a sentence and their relation with each other. The objective of syntactic analysis is to find syntactic structure of a grammar of a natural language. Natural language processing is an area of computer science and linguistics, concerned with the dealings amongst computers and human languages. It processes the data through lexical analysis, Syntax analysis and Semantic analysis. This paper gives various parsing methods. The algorithm specified in the paper splits the English sentences into parts using POS tagger and then parses these sentences using grammar rules of Natural language.